A comparison of tarsal morphology and traction force in the two burying beetles Nicrophorus nepalensis and Nicrophorus vespilloides (Coleoptera, Silphidae) - Schnee, Liesa; Sampalla, Benjamin; Müller, Josef K.; Betz, Oliver (Beilstein Journal of Nanotechnology, 2019)
Our aim was to compare friction and traction forces between two burying beetle species of the genus Nicrophorus exhibiting different attachment abilities during climbing. Specifically, the interaction of adhesive hairs and claws during attachment with respect to various surface properties was investigated by using a 2 × 3 experimental design. Traction force was measured for two different surface energies (hydrophilic vs hydrophobic) varying in roughness from smooth to micro-rough to rough. Nanotribometric tests on single legs were also performed. The external morphology of the attachment devices investigated by scanning electron microscopy suggested higher intra-specific (intersexual) than inter-specific differences. Whereas differences between the two species in traction force were high on smooth surfaces, no differences could be detected between males and females within each species. With claws intact, both species showed the highest forces on rough surfaces, although N. nepalensis with clipped claws performed best on a smooth surface. However, N. nepalensis beetles outperformed N. vespilloides, which showed no differences between smooth and rough surfaces with clipped claws. Both species demonstrated poor traction forces on micro-rough surfaces. Results concerning the impact of surface polarity were inconclusive, whereas roughness more strongly affected the attachment performance in both species. Nanotribometric analyses of the fore tarsi performed on micro-rough and rough surfaces revealed higher friction in the proximal (pull) direction compared with the distal (push) direction. In these experiments, we detected neither differences in friction performance between the two species, nor clear trends concerning the influence of surface polarity. We conclude that the investigated morphological traits are not critical for the observed interspecific difference in attachment ability on smooth surfaces. Furthermore, interspecific differences in performance are only clear on smooth surfaces and vanish on micro-rough and rough surfaces. Our results suggest that even subtle differences in the adhesion-mediating secretion in closely related species might result in qualitative performance shifts.
Keywords: adhesion; friction; Insecta; locomotion; tarsus